Mosby's physical examination DVD series : DVD 6 : chest and lungs [ - Ball, Jane; Benedict, G. William; Dains, Joyce E.; Seidel, Henry M. (Mosby's physical examination DVD series, 2006)
"This 16 minute video shows the steps needed to examine the chest and lungs, including the proper use of equipment. With the patient seated, it demonstrates how to inspect the patient's chest and respiratory pattern, perform palpation, and percuss and auscultate following a systematic pattern. The video shows expected findings and alerts the viewer to selected variations in pediatric and geriatric patients. In addition, it identifies vesicular, bronchovesicular, bronchial, and adventitious sounds."--Publisher's website